Opfer der Motorisierung. Versuch einer konkreten Schätzung. - Gietinger, Klaus (Deutscher Verkehrs-Verl., 2006)
Bisher waren Schätzungen der Gesamtzahl aller Straßenverkehrsopfer weltweit relativ ungenau. Durch bessere Datenerfassung und neuere Studien konnten in den vergangenen Jahren die Dunkelziffern präziser bestimmt werden. Prognosen lassen einen starken Anstieg der globalen Unfallraten erwarten. difu

Former estimates of total global road fatalities have been unsafe at any time. Newer studies found on better database make better estimates real. Underestimation could be fixed. Result: About 35 million people died in road crashes since invention of motor vehicles, over 1,2 billion were injured. The global risk of being killed by road crash is increasing and will be in 2030 one of the highest risks ever. The numbers of victims (annual and total) will be doubled then. difu
Keywords: Öffentlicher Verkehr; Straßenverkehr; Unfall; Verkehrsunfall; Verkehrsstatistik; Verkehrsforschung; Unfallstatistik